EVALUATION OF TENDENCY TO BLACKSPOT BRUISING AND ENZYMATIC DISCOLORATION OF POTATO TUBERS - Hara-Skrzypiec, Agnieszka (Plant Breeding and Seed Science, 2017)
Enzymatic discoloration of potato tubers initiated by mechanical impact bruising and the discoloration which appears after tuber cutting are crucial quality traits of the cultivated potato. The presented determina-tion of blackspot bruise susceptibility includes evaluation of the trait with two impact methods – the rotating drum and the falling bolt. These two methods affect both the physical and the biochemical properties of tu-bers. Evaluation of the discoloration potential after tuber cutting (ED) is also discussed. Evaluating the discol-oration potential of tubers is one of the most important points in determining potato quality.